Transferability of antibiotic resistance determinants in strains of Staphylococcus aureus belonging to different phage groups - Janosek, J; Simkovicová, M (Journal of hygiene, epidemiology, microbiology, and immunology, 1983)
A total of 107 donor strains of Staphylococcus aureus isolated from clinical material, with a high incidence of multiresistant strains belonging predominantly to phage group III, were tested for transmission of determinants of resistance to 6 antibiotics using mixed cultures of donor strains and the recipient Staphylococcus aureus strain 5849-fur-r, rif-r. The capability of strains to transfer resistance markers to the recipient was found to depend neither on phage group nor phage type to which the donor strain belonged, but strains possessing multiple resistance to antibiotics effectuated transfers at comparatively higher frequencies.
Keywords: Bacteriophage Typing; antibakteriální látky; antibiotická rezistence; Anti-Bacterial Agents; R Factors; Staphylococcus aureus; Statistics as Topic; R-plasmidy; Drug Resistance, Microbial; statistika jako téma; fagotypizace; stafylokokové bakteriofágy; Staphylococcus Phages